Relationship between Informational Books Attraction and Reading Attitude and Behavior of Students at Elementary School - Tri Mega Asri (Program Pendidikan Vokasi Universitas Brawijaya, 2013)
Informational books are published to fulfill children’s needs. The presence of informational books can transfer knowledge that children want to know related to science and all things which exist and happen around them. As a means of communication, books have big influence in determining attitude and behavior. Thus, it is important to have study on how far informational books attraction influences students’ reading attitude and behavior. In order to get ordinal-scale data, this study applies Likert scale measurement and correlational method by using Spearman Rank in SPSS program. The data were collected through questionnaire distributed to 60 respondents, interview, observation and review of related literature. To conclude, attraction of informational books influences reading attitude and behavior of students at SDN. Melong Mandiri 1 Cimahi